Profile of deaths due to electrocution– a retrospective study conducted at a tertiary care hospital in Haryana (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Background- Deaths due to electrocution have been on an increase due to extensive  use of modern electrical appliances in day-to-day work. Electrical burns are associated  with severe morbidity and high mortality. However, these are preventable if proper  safety measures are taken while using them.  Methods- This study took into account 61 post-mortem records of cases conducted in  7 years and analysed cases of deaths caused by electrocution in the region.  Results- Of the 61 cases most common occurrence of deaths by electrocution was  seen in rainy season and most commonly affected areas were upper extremities. Conclusion- The study highlights that the death caused by electrocution are not so  common and also avoidable if proper care is taken while working around electrical  appliances. Safety measures should be instructed properly to avoid such hazards.
Keywords: Electrocution, Electrical Injury, Accidental, Exit and entry wound, Rainy season.